Penerapan Model Pembelajaran Guided Inquiry Untuk Meningkatkan Keterampilan Komunikasi Siswa Kelas VII SMP Negeri 14 Lubuklinggau - Diana; Tri Ariani; Endang Lovisa (Proceeding of Silampari Conference of Life Science and Technology, 2026)
This study aims to determine the improvement in communication skills among 7th-grade students at SMP Negeri 14 Lubuklinggau through the implementation of the Guided Inquiry learning model within the topic of Motion and Force. A quantitative research method was employed, utilizing a pre-experimental design—specifically, the One-Group Pretest-Posttest Design. The research subjects consisted of 30 students from class VII.1, selected via simple random sampling from a total population of 156 7th-grade students. Data on communication skills were collected using an observation sheet covering five indicators: listening and showing respect, self-confidence, effectively conveying ideas, taking responsibility for ideas, and communicating effectively. Data analysis was conducted using descriptive percentage analysis. The results indicate a gradual improvement in students' communication skills: the average score rose from 63.33% in the first meeting to 83.33% in the second, reaching 85.00% in the third, ultimately placing the students in the